Transcobalamin II receptor polymorphisms are associated with increased risk for neural tube defects. Issue 10 (24th June 2010) - Pangilinan, F; Mitchell, A; VanderMeer, J; Molloy, A M; Troendle, J; Conley, M; Kirke, P N; Sutton, M; Sequeira, J M; Quadros, E V; Scott, J M; Mills, J L; et al.
Abstract : Objective: Women who have low cobalamin (vitamin B12 ) levels are at increased risk for having children with neural tube defects (NTDs). The transcobalamin II receptor ( TCblR ) mediates uptake of cobalamin into cells. Inherited variants in the TCblR gene as NTD risk factors were evaluated. Methods: Case–control and family-based tests of association were used to screen common variation in TCblR as genetic risk factors for NTDs in a large Irish group. A confirmatory group of NTD triads was used to test positive findings. Results: 2 tightly linked variants associated with NTDs in a recessive model were found: TCblR rs2336573 (G220R; pcorr =0.0080, corrected for multiple hypothesis testing) and TCblR rs9426 (pcorr =0.0279). These variants were also associated with NTDs in a family-based test before multiple test correction (log-linear analysis of a recessive model: rs2336573 (G220R; RR=6.59, p=0.0037) and rs9426 (RR=6.71, p=0.0035)). A copy number variant distal to TCblR and two previously unreported exonic insertion–deletion polymorphisms were described. Conclusions: TCblR rs2336573 (G220R) and TCblR rs9426 represent a significant risk factor in NTD cases in the Irish population. The homozygous risk genotype was not detected in nearly 1000 controls, indicating that this NTD risk factor may be of low frequency and high penetrance. 9 other variants are in perfect linkage disequilibrium with the associated single nucleotide polymorphisms. Additional work is required to identify the disease-causing variant. Our data suggest that variation in TCblR plays a role in NTD risk and that these variants may modulate cobalamin metabolism.